IMPLEMENTASI KEGIATAN PEMBIASAAN KEAGAMAAN DALAM MEMBENTUK KARAKTER RELIGIUS PESERTA DIDIK DI SD ISLAM AL CHUSNAINI - Ikhfinaz Zahroh; Taufik Taufik; Nur Romdlon Maslahul Adi; M. Dani Karismawan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to describe the implementation of religious habituation activities and their role in shaping the religious character of students at Al Chusnaini Islamic Elementary School located in Sidoarjo Regency. The research used a qualitative approach with an ethnographic type. Ethnography is research that focuses on describing and understanding the culture of a group comprehensively through long-term participant observation. Data collection techniques were carried out through participatory observation, in-depth interviews with supervising teachers, classroom teachers, and documentation during the four-month teaching assistance activities. The results of the study indicate that religious practices carried out regularly and consistently, such as congregational prayers, recitation of the Qur'an, and communal prayers, are able to instill religious values such as discipline, honesty, responsibility, and politeness in students. Supporting factors for success include the involvement of teachers as role models, a conducive school environment, and the role of parents. Meanwhile, the main challenges stem from a lack of awareness among students, differences in family backgrounds, and negative influences from the outside environment. Thus, religious habituation is an effective strategy in religious character education if it is implemented in an integrated and sustainable manner.